OVERWEIGHT IN PREGNANT WOMEN ATTENDING HEALTH CENTERS IN COLOMBO, PARANÁ, BRAZIL - Fernanda Manera; Doroteia Aparecida Hofelmann (Universidade do Estado do Rio de Janeiro, 2019)
Objective: To estimate the prevalence of overweight in pregnant women and associate it with socio-economic and demographic variables, obstetric history and pregestational overweight in pregnant women attending health centers in the city of Colombo, in Brazil. Methods: We used a questionnaire to collect the data between April and November 2016. Three hundred and sixteen pregnant women between 18 and 46 years old were included in our study. Results: The prevalence of gestational overweight was 46.2%. In the adjusted analysis, that prevalence was higher in pregnant women between 20 and 34 years old (PR 1.72; CI 95% 1.04-2.83) and over 35 years old (PR 2.08; CI 95% 1.18-3.66),in women with higher parity (three or more pregnancies - PR 1.47; CI 95% 1.04-2.09) and those whopresented pregestational overweight (PR 5.09; CI 95% 3.63-7.14). Among the smokers, there was a lower prevalence of overweight (PR 0.45; CI 95% 0.23-0.89).Conclusion: Monitoring pregestational weight and weight gain during pregnancy is extremely important for primary care and it is recommended that women have an adequate weight before their pregnancy. DOI: 10.12957/demetra.2019.36842